Adolescents' and Young Adults' Online Risk Taking: The Role of Gist and Verbatim Representations. Issue 8 (27th March 2015) - White, Claire M.; Gummerum, Michaela; Hanoch, Yaniv
Abstract : Young people are exposed to and engage in online risky activities, such as disclosing personal information and making unknown friends online. Little research has examined the psychological mechanisms underlying young people's online risk taking. Drawing on fuzzy trace theory, we examined developmental differences in adolescents' and young adults' online risk taking and assessed whether differential reliance on gist representations (based on vague, intuitive knowledge) or verbatim representations (based on specific, factual knowledge) could explain online risk taking. One hundred and twenty two adolescents (ages 13–17) and 172 young adults (ages 18–24) were asked about their past online risk‐taking behavior, intentions to engage in future risky online behavior, and gist and verbatim representations. Adolescents had significantly higher intentions to take online risks than young adults. Past risky online behaviors were positively associated with future intentions to take online risks for adolescents and negatively for young adults. Gist representations about risk negatively correlated with intentions to take risks online in both age groups, while verbatim representations positively correlated with online risk intentions, particularly among adolescents. Our results provide novel insights about the underlying mechanisms involved in adolescent and young adults' online risk taking, suggesting the need to tailor the representation of online risk information to different age groups.